The effects of sexual violence on psychosocial outcomes in formerly abducted girls in Northern Uganda: the WAYS study - Amone-P’Olak, Kennedy; Ovuga, Emilio; Jones, Peter Brian (BMC psychology, 2015)
The objective of this study is to investigate the effects of sexual violence on the odds of different psychosocial outcomes (depression, psychotic symptoms, somatic complaints, conduct problems, daily functioning, community relations, and stigma) among formerly abducted girls in Uganda. Methods: Data from an on-going War-Affected Youth Study (WAYS) in Uganda was used to compute the prevalence of psychosocial problems (scores ≥ 75th percentile) among three categories of formerly abducted girls (1) no history of sexual violence without children, 2) a history of sexual violence without children, and 3) a history of sexual violence with children as a consequence) among 210 women (age 22.06, SD = 2.06, range 18–25). Multiple logistic regression analyses were used to examine differences in psychosocial outcomes by the different categories of formerly abducted girls. Results: Compared to participants with no history of sexual violence and without any children, the odds of adverse psychosocial outcomes were increasingly higher for all psychosocial dimensions for those who reported sexual violence with or without children. Those with a history of sexual violence and with children as a consequence had more than five times the odds of reporting depressive symptoms (OR, 5.37; 95 % CI (1.45–19.90), somatic complaints (OR, 6.59; 95 % CI (1.80 – 24.11), and stigma (OR, 13.85; 95 % CI (3.73 – 51.42) compared to those who did not report sexual violence. Conclusion: This study highlighted the risks of psychosocial problems among different categories of formerly abducted girls regarding sexual violence. Vulnerability to psychosocial problems among formerly abducted girls is further compounded by sexual violence, child care, stigma, and poverty.
Keywords: Sexual violence; Psychosocial outcomes; Abducted girls; Northern Uganda